Predicting Probable Roof Fall Areas In Advance Of Mining By Geological Analysis - W. K. Overbey (The National Institute for Occupational Safety and Health (NIOSH), 1973)
Surface fracture trace density, changes in roof rock type, and topographic unloading due to drainage were mapped for the mining areas located in the Blacksville-Osage, W. Va., quadrangles to investigate their influence on mine roof falls. Using these factors, a technique was developed to predict probable roof fall areas ahead of projected mining operations. As a feasibility test of this proposed technique, areas were delineated where one, two, and all three of these factors were operating to formulate a "potential hazard map" for comparison with roof fall observations that were made. The limited evidence suggests that in combination these factors are reliable predictors of where roof falls are likely to occur. This technique promises to be a useful tool in planning mining operations.